The proteoglycan mimecan is associated with carotid plaque vulnerability and increased risk of future cardiovascular death. (November 2020) - Tengryd, Christoffer; Nielsen, Signe Holm; Cavalera, Michele; Bengtsson, Eva; Genovese, Federica; Karsdal, Morten; Dunér, Pontus; Orho-Melander, Marju; Nilsson, Jan; Edsfeldt, Andreas; Gonçalves, Isabel
Abstract: Background and aims: A vulnerable plaque is an atherosclerotic plaque that is rupture-prone with a higher risk to cause cardiovascular symptoms such as myocardial infarction or stroke. Mimecan or osteoglycin is a small leucine-rich proteoglycan, important for collagen fibrillogenesis, that has been implicated in atherosclerotic disease, yet the role of mimecan in human atherosclerotic disease remains unknown. Methods: 196 human atherosclerotic carotid plaques were immunostained for mimecan. Smooth muscle cells, macrophages and intraplaque haemorrhage were also measured with immunohistochemistry. Neutral lipids were stained with Oil Red O and calcium deposits were quantified. Plaque homogenate levels of MCP-1, IL-6 and MIP-1β were measured using a Proximity Extension Assay and MMP-9 levels were measured using Mesoscale. Glycosaminoglycans, collagen and elastin were assessed by colorimetric assays and TGF-β1, β2 and β3 were measured using a multiplex assay. Mimecan gene expression in THP-1 derived macrophages was quantified by qPCR and protein expression in vitro was visualized with immunofluorescence. Cardiovascular events were registered using medical charts and national registers during follow-up. Results: Mimecan correlated positively with plaque area of lipids, macrophages, intraplaque haemorrhage and inversely with smooth muscle cell staining. Mimecan also correlated positively with plaque levels of MMP-9 and MCP-1. Mimecan was upregulated in THP-1 derived macrophages upon stimulation with MCP-1. Patients with high levels of mimecan (above median) had higher risk for cardiovascular death. Conclusions: This study indicates that mimecan is associated with a vulnerable plaque phenotype, possibly regulated by plaque inflammation. In line, plaque levels of mimecan independently predict future cardiovascular death. Graphical abstract: Image 1 Highlights: Mimecan correlates with vulnerable histological features in human carotid plaques. Mimecan correlates with extracellular matrix degrading enzyme MMP-9. In vitro stimulation with MCP-1 increases mimecan expression in macrophages. High levels of mimecan in carotid plaques predict future cardiovascular death.